(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Considering the constant improvement of technological possibilities, there is no doubt that the Internet has been gaining the title of one of the most attractive channel of direct interactive marketing. Regardless, certain weaknesses are attributed to digital medias, whose power results in a negative impact on consumer’s attitudes. In line with that, a subject of the paper is direct marketing communication with special reference to electronic mail, in order to identify the behavior of target groups and create optimal communication strategies. The research problem is classification of promotional e-mail messages in the spam section, in other words the perception as a set of junk mail. According to the HubSpot Academy, the high frequency of sending messages had caused the e-mail subscriptions cancellation of 51% of consumers who are in the databases of specific companies. Empirical research was conducted on the teritory of the Republic of Serbia on a sample of 100 respondents. After applying Pearson’s correlation test, consumer’s viewpoints about the aggressiveness of e-mail campaigns had been analyzed.